Transfusion of fresh‐frozen plasma in critically ill patients with a coagulopathy before invasive procedures: a randomized clinical trial (CME). Issue 1 (9th June 2014) - Müller, Marcella C.; Arbous, M. Sesmu; Spoelstra‐de Man, Angelique M.; Vink, Roel; Karakus, Atilla; Straat, Marleen; Binnekade, Jan M.; de Jonge, Evert; Vroom, Margreeth B.; Juffermans, Nicole P.
<x xml:space="preserve">Abstract</x> Background Prophylactic use of fresh‐frozen plasma (FFP) is common practice in patients with a coagulopathy undergoing an invasive procedure. Evidence that FFP prevents bleeding is lacking, while risks of transfusion‐related morbidity after FFP have been well demonstrated. We aimed to assess whether omitting prophylactic FFP transfusion in nonbleeding critically ill patients with a coagulopathy who undergo an intervention is noninferior to a prophylactic transfusion of FFP. Study Design and Methods A multicenter randomized open‐label trial with blinded endpoint evaluation was performed in critically ill patients with a prolonged international normalized ratio (INR; 1.5‐3.0). Patients undergoing placement of a central venous catheter, percutaneous tracheostomy, chest tube, or abscess drainage were eligible. Patients with clinically overt bleeding, thrombocytopenia, or therapeutic use of anticoagulants were excluded. Patients were randomly assigned to omitting or administering a prophylactic transfusion of FFP (12 mL/kg). Outcomes were occurrence of postprocedural bleeding complications, INR correction, and occurrence of lung injury. Results Due to slow inclusion, the trial was stopped before the predefined target enrollment was reached. Eighty‐one patients were randomly assigned, 40 to FFP and 41 to no FFP transfusion. Incidence of bleeding did not differ between groups, with a total of one major and 13 minor bleedings (p = 0.08 for noninferiority). FFP transfusion resulted in a reduction of INR to less than 1.5 in 54% of transfused patients. No differences in lung injury scores were observed. Conclusion In critically ill patients undergoing an invasive procedure, no difference in bleeding complications was found regardless whether FFP was prophylactically administered or not.